QT-Interval Prolongation in the Treatment of Drug-Resistant Tuberculosis - A. V. Kukurika (Антибиотики и Химиотерапия, 2024)
The review analyzes the research articles, guidelines, and clinical trial results on the eﬀect of ﬂuoroquinolones, bedaquiline, nitroimidazoles, and clofazimine on QTc prolongation. The importance of timely and regular monitoring of cardiotoxicity and the importance of continuing clinical trials for the discovery of anti-tuberculosis drugs with a satisfactory safety proﬁle are presented.